Screening of ZAT12 and GlyII wheat transgenics using seedling based assays for stress tolerance - Bhowmick, Pradipta; Suneja, Yadhu Suneja; Srivastava, Puja; Sharma, Achla; Bains, Navtej Singh (Journal of Cereal Research, 2016)
Single copy transgenics of Agrobacterium mediated wheat transformantswere available for two genes- Zat12 and GlyII in the background ofwheat cultivar DPW 621-50. Three homozygous transgenic linescarrying ZAT12 and three carrying GlyII were subjected to preliminaryscreening for water deficit and salinity stress respectively. An initialexperiment was carried out to standardize the concentrations of PEGand NaCl using parental non- transformed line DPW 621-50. Seedlingswere grown in vermiculite in propagation trays in a growth chambermaintained at 200C Â± 20C, 8/16 hours dark/light ZAT 12 homozygousprogenies were screening using PEG at 25% and 30% concentration.Transgenics Z-8-12 and Z-15-10 showed significant improvement forshoot and root traits under PEG induced water deficit stress. In thebest transgenic line, 45%, 20%, 33%, 22%, 24%and 20% improvementover DPW 621-50 was observed for root length, shoot length, freshroot weight, root dry weight, shoot fresh weight and shoot dry weightrespectively under stress conditions. In a parallel experiment, allthe three GlyII transgenics showed marked superiority over parentalcultivar DPW 621-50. The best GlyII transgenic showed 25%, 19%,12%, 22%, 26% and 22% improvement over PBW 621 for root length,shoot length, fresh root weight, root dry weight, shoot fresh weightand shoot dry weight respectively under stress conditions.